2019
DOI: 10.1038/s41598-019-51572-4
|View full text |Cite
|
Sign up to set email alerts
|

Rising CO2 enhances hypoxia tolerance in a marine fish

Abstract: Global environmental change is increasing hypoxia in aquatic ecosystems. During hypoxic events, bacterial respiration causes an increase in carbon dioxide (CO2) while oxygen (O2) declines. This is rarely accounted for when assessing hypoxia tolerances of aquatic organisms. We investigated the impact of environmentally realistic increases in CO2 on responses to hypoxia in European sea bass (Dicentrarchus labrax). We conducted a critical oxygen (O2crit) test, a common measure of hypoxia tolerance, using two trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…However, fish have well developed acid-base regulatory mechanisms and blood sampling showed that sea bass in normoxia had fully compensated for the effects of increased environmental CO 2 on blood pH by compensatory accumulation of extra HCO 3 - , resulting in no changes in Hb-O 2 binding affinity (Figure 5 and S1). Additionally, we have recently shown that sea bass are able regulate blood pH when exposed to concurrent progressive hypercapnia during progressive hypoxia over the course of several hours and have higher Hb-O 2 binding affinity in these conditions when compared to fish exposed to progressive hypoxia with no concurrent hypercapnia (Montgomery et al, 2019). In addition, we did not see significant changes in Hb levels or Hct between CO 2 treatments (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, fish have well developed acid-base regulatory mechanisms and blood sampling showed that sea bass in normoxia had fully compensated for the effects of increased environmental CO 2 on blood pH by compensatory accumulation of extra HCO 3 - , resulting in no changes in Hb-O 2 binding affinity (Figure 5 and S1). Additionally, we have recently shown that sea bass are able regulate blood pH when exposed to concurrent progressive hypercapnia during progressive hypoxia over the course of several hours and have higher Hb-O 2 binding affinity in these conditions when compared to fish exposed to progressive hypoxia with no concurrent hypercapnia (Montgomery et al, 2019). In addition, we did not see significant changes in Hb levels or Hct between CO 2 treatments (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…For each treatment all respirometry measurements were conducted in two groups (hereafter referred to as respirometry group), with five fish being measured simultaneously for each group. Following the 12 hour acclimation period we measured ṀO 2 of each sea bass for ∼3-4 hours (from ∼6 am to ∼10 am) before hypoxia tolerance was assessed using a critical O 2 tension (O 2crit ) trial (Figure 6), following protocols set out in Montgomery et al (2019). Carbon dioxide levels in the water were simultaneously increased as O 2 declined during O 2crit trials to reflect the natural rise in CO 2 during hypoxic events in aquatic systems (Melzner et al, 2013; Montgomery et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Mayol et al 36 demonstrated that high p CO 2 further challenges respiration in the NHCS. However, recent evidence in fish shows that they are better adapted to tolerate hypoxia under elevated CO 2 conditions as compared to hypoxia alone 64 . Certainly, the effects of p CO 2 and p O 2 cannot be considered independently, as they co-occur in nature and are both involved in respiratory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of other marine organisms have documented favorable impacts of reduced pH in combination with low oxygen as well. For example, Montgomery et al (2019) found that lower pH increased hypoxia tolerance in a fish, due to increased affinity of red blood cells for oxygen under the lower pH conditions. Invertebrates that lack hemoglobin have also shown positive impacts of reduced pH.…”
Section: Impacts Of Multiple Stressorsmentioning
confidence: 99%